2019
DOI: 10.3390/atmos10100603
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Particle and Black Carbon Emission Factors of Vehicular Fleet in Manila, Philippines

Abstract: Poor air quality has been identified as one of the main risks to human health, especially in developing regions, where the information on physical chemical properties of air pollutants is lacking. To bridge this gap, we conducted an intensive measurement campaign in Manila, Philippines to determine the emission factors (EFs) of particle number (PN) and equivalent black carbon (BC). The focus was on public utility jeepneys (PUJ), equipped with old technology diesel engines, widely used for public transportation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…The source factor names were determined based on the enhancement of the following species ( Fig. 4): (i) crustal (Al, Ti) (Harrison et al, 2011;Malm et al, 1994;Singh et al, 2002); (ii) biomass burning (K, Rb) (Andreae, 1983;Artaxo et al, 1994;Braun et al, 2020;Chow et al, 2004;Echalar et al, 1995;Ma et al, 2019;Schlosser et al, 2017;Thepnuan et al, 2019;Yamasoe et al, 2000); (iii) sea salt (Na, Cl) (Seinfeld and Pandis, 2016); (iv) combustion (V, Ni, As) (Allen et al, 2001;Linak et al, 2000;Mahowald et al, 2008;Mooibroek et al, 2011;Prabhakar et al, 2014;Wasson et al, 2005); and (v) waste processing (Cd, Pb) (Cruz et al, 2019;Gullett et al, 2007;Iijima et al, 2007;Pabroa et al, 2011). While both SO 2− 4 and NO − 3 are secondarily produced, the latter is more commonly linked to supermicrometer particles (Allen et al, 1996;Dasgupta et al, 2007;Fitzgerald, 1991;Maudlin et al, 2015), including in the study region (Cruz et al, 2019).…”
Section: Source Apportionmentmentioning
confidence: 99%
“…The source factor names were determined based on the enhancement of the following species ( Fig. 4): (i) crustal (Al, Ti) (Harrison et al, 2011;Malm et al, 1994;Singh et al, 2002); (ii) biomass burning (K, Rb) (Andreae, 1983;Artaxo et al, 1994;Braun et al, 2020;Chow et al, 2004;Echalar et al, 1995;Ma et al, 2019;Schlosser et al, 2017;Thepnuan et al, 2019;Yamasoe et al, 2000); (iii) sea salt (Na, Cl) (Seinfeld and Pandis, 2016); (iv) combustion (V, Ni, As) (Allen et al, 2001;Linak et al, 2000;Mahowald et al, 2008;Mooibroek et al, 2011;Prabhakar et al, 2014;Wasson et al, 2005); and (v) waste processing (Cd, Pb) (Cruz et al, 2019;Gullett et al, 2007;Iijima et al, 2007;Pabroa et al, 2011). While both SO 2− 4 and NO − 3 are secondarily produced, the latter is more commonly linked to supermicrometer particles (Allen et al, 1996;Dasgupta et al, 2007;Fitzgerald, 1991;Maudlin et al, 2015), including in the study region (Cruz et al, 2019).…”
Section: Source Apportionmentmentioning
confidence: 99%
“…Here, the main source of eBC particles is traffic due to the lenient regulation of vehicular emissions and high volume of vehicles. For more information on MACE-2015, the readers are directed to the following publications (Kecorius et al, 2017;Alas et al, 2018;Kecorius et al, 2018;Kecorius et al, 2019;Madueño et al, 2019). Reference instruments were set-up permanently (for the duration of the experiment) inside a building within an urban background area (university campus).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been found that annual anthropogenic BC emissions increased from 6.6 to 7.2 Tg during 2000-2010 (Klimont et al, 2017). Moreover, due to rapid urbanization in many developing regions like China, South Asia, and Southeast Asia, the total aerosol mass constitutes a significantly large portion of BC (Kumar et al, 2018;Bond et al, 2007;Wiedensohler et al, 2018;Madueño et al, 2019Madueño et al, , 2020. In addition to the warming effect, BC also decreases snow albedo (Doherty et al, 2010), causes adverse health effects (Janssen et al, 2011), and lowers visibility (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%